2018
DOI: 10.1111/ejn.14082
|View full text |Cite
|
Sign up to set email alerts
|

Initial rewarding effects of cocaine and amphetamine assessed in a day using the single‐exposure place preference protocol

Abstract: In rodents, only a single dose of cocaine or amphetamine is required to cause a marked increase in extracellular dopamine, induce hyperlocomotion and cause persistent plasticity changes within dopaminergic neurons of the ventral tegmental area (VTA). The initial drug experience is suggested to predict vulnerability of developing addiction, but only few studies have assessed the perception of reward accompanying this initial exposure. We recently presented an approach to assess the initial rewarding effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Moreover, dopamine is critically involved in a number of processes that all shape goal‐directed behavior: de novo learning, updating behavior in light of changing rewards or environments, action selection and initiation. While it is possible to dissect experimentally these phenomena, eg, by studying action initiation, 58 by differentiating valence from salience, ie, “liking” from “wanting,” or motivation to pursue a reward, 66,67 and by studying differential receptor mechanisms engaged in expression versus acquisition of learned behavior, 68 bottom‐up manipulation of these components by modulation of the VTA is an ongoing challenge. With the recent advent of advanced intersectional genetic tools, and resulting characterization of different populations of VTA DA neurons exhibiting different properties 69 and projecting to different output structures, 70 such manipulations will be much more practical.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dopamine is critically involved in a number of processes that all shape goal‐directed behavior: de novo learning, updating behavior in light of changing rewards or environments, action selection and initiation. While it is possible to dissect experimentally these phenomena, eg, by studying action initiation, 58 by differentiating valence from salience, ie, “liking” from “wanting,” or motivation to pursue a reward, 66,67 and by studying differential receptor mechanisms engaged in expression versus acquisition of learned behavior, 68 bottom‐up manipulation of these components by modulation of the VTA is an ongoing challenge. With the recent advent of advanced intersectional genetic tools, and resulting characterization of different populations of VTA DA neurons exhibiting different properties 69 and projecting to different output structures, 70 such manipulations will be much more practical.…”
Section: Discussionmentioning
confidence: 99%
“…Initial perception of the drugs was measured by single exposure place preference experiments performed in an elongated three compartment apparatus (67.5 cm x 24 cm) with a biased design of different floor textures and wall pattens and a neutral zone in the middle. We have previously shown that mice of both genders exhibit a strong bias towards the striped compartment, and that a single exposure of psychostimulants in the grey compartment sufficiently changes the preference towards that compartment (Jensen et al ., 2021; Runegaard et al ., 2017; Runegaard et al , 2019). For further details of the setup, we refer to (Runegaard et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Of significant interest from a preclinical perspective, mechanistic approaches further used a behavioural biomarker (demand for cocaine) to predict progression to addiction and response to treatment with orexin‐based therapies (James et al ., ). Efforts to avoid repeated drug injections and to allow assessment of initial subjective reward perception, in mice produced a condensed version of a place preference protocol, showing that a single exposure to both cocaine and amphetamine is sufficient to induce place preference (Runegaard et al ., ). These data also suggest that measuring VTA DA signalling prior to drug exposure can add to the tools available to further decipher the complex mechanisms underlying the progression from initial drug experience to escalating drug intake and addiction.…”
Section: Preclinical Modelsmentioning
confidence: 97%